Future perspectives: United Kingdom National Multidisciplinary Guidelines - King, E V (J Laryngol Otol, 2016)
The multidisciplinary management of head and cancer has changed radically in the last decade. This paper provides a glimpse of the emerging surgical and oncological interventions that may play major roles in the treatment paradigms of tomorrow.